Flash Service Training Model For Beginner Athletes - Dadang Budi Hermawan; Wawan Eka Setiawan (Jurnal Edukasi Sebelas April, 2021)
The purpose of this study was to produce a Sepak Takraw Service training model for beginner athletes in Sumedang Regency. In addition, the research was conducted to obtain more in-depth and accurate information about the application of the training model, as well as the effectiveness and efficiency of the training model made. This research and research method uses Research & Development (R & D) development from Borg and Gall. The sample of this study is beginner athletes who are members of the sepak takraw club in Sumedang district. The results of this study are a variety of exercises and the creation of ball delivery aids to help trainers to train athletes, and accelerate the increase in the ability of athletes to achieve optimal sepak takraw service competencies. This includes six variations of corner soccer service practice (Coerner). In the test of the significance of differences with SPSS 21 For Windows IMB, the results of t-count = -111,387 df = 49 and p-value = 0.00 <0.05. This means, there is a significant difference between service ability before and after being given treatment, namely the application of sepak takraw service training model for beginner athletes in Sumedang Regency. Based on this information, it can be said that the training model for beginner athletes who are developed is effective and can improve sepak takraw's service ability optimally